Panacea for the refugee crisis? Rethinking the promotion of ‘self-reliance’ for refugees - Easton-Calabria, E; Omata, N (Taylor and Francis, 2018)
This article provides a critical examination of the current extensive promotion of ‘self-reliance’ for refugees. The existing scholarship largely ignores the unsuccessful historical record of international assistance to foster refugees’ self-reliance and fails to discuss its problematic linkages to neoliberalism and the notion of ‘dependency’. The article reveals that the current conceptualisation and practice of self-reliance are largely shaped by the priorities of international donors that aim to create cost-effective exit strategies from longterm refugee populations. The authors argue that where uncritically interpreted and applied, the promotion of self-reliance can result in unintended and undesirable consequences for refugees’ well-being and protection.